1972
DOI: 10.1530/jrf.0.0290105
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Sheep Eggs in the Rabbit Oviduct and Their Viability After Re-Transfer to Ewes

Abstract: Sheep eggs recovered from the rabbit's oviduct were re-transferred to ewes which had been in oestrus within 24 hr of the original donor ewes. The highest survival rates to lambing were obtained when eggs were re-transferred to recipient ewes after 3 days in the rabbit. The best rate of survival (69 %) was with two-and four-cell eggs which had been in pseudopregnant rabbits for 3 days.The proportion ofthe re-transferred eggs which survived declined when the period in the rabbit oviduct was extended from 3 to 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The oviductal environment can support embryonic growth up to the blastocyst stage across a wide range of species following transspecies transfer. Ligated rabbit oviducts have been used extensively for the development of embryos from many species including sheep [6,43], cattle [9,20,74], and recovery at Day 14, demonstrating that bovine embryos can undergo continued development in the reproductive tract of ewes when transferred either as 4-cell embryos or as expanded or hatched blastocysts.…”
Section: Embryo Culture In Vivo Vs In Vitromentioning
confidence: 99%
“…The oviductal environment can support embryonic growth up to the blastocyst stage across a wide range of species following transspecies transfer. Ligated rabbit oviducts have been used extensively for the development of embryos from many species including sheep [6,43], cattle [9,20,74], and recovery at Day 14, demonstrating that bovine embryos can undergo continued development in the reproductive tract of ewes when transferred either as 4-cell embryos or as expanded or hatched blastocysts.…”
Section: Embryo Culture In Vivo Vs In Vitromentioning
confidence: 99%
“…Moreover, the containers used are costly and should be returned with the concomitant expense. Some approaches have explored the feasibility of alternative methods using, for instance, intermediate recipients [2-4], or specific temperatures [5,6]. In these studies, 2-cell embryos were used, even though embryos of certain mice strains are prone to 2-cell blockage when cultured in suboptimal conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to have particles of various origins (Greenwald 1958; Hodgson et al. 1976; Denker 1982; Bourdage and Halbert 1984) and ova and embryos derived from other species (Lawson et al. 1972; Sirard et al.…”
Section: Introductionmentioning
confidence: 99%
“…This might contribute to failure in the establishment of pregnancy when transferring in vitro-cultured rabbit embryos (Seidel et al 1976;Binkerd and Anderson 1979). Attempts to have particles of various origins (Greenwald 1958;Hodgson et al 1976;Denker 1982;Bourdage and Halbert 1984) and ova and embryos derived from other species (Lawson et al 1972;Sirard et al 1985;Kasai et al 1993) encased in mucin by introducing them into a rabbit oviduct, have been successful in most, but not all cases (Yoshinaga and Adams 1967). Kasai et al (1993) found that the mucin coat may help rabbit and, under certain conditions also mouse embryos, to resist damage during refrigeration.…”
Section: Introductionmentioning
confidence: 99%